Shamballa, Heaven can wait. How 3D printing will sustain the future - Dario Russo; Massimo Moretti (Agathón)
This article is devoted to the activities of the WASP group of which Massimo Moretti is the founder, and emphasizes how it is possible to reconcile technological progress with the creation of a heaven on earth: a society of equals, eco-compatible, scientifically evolved and completely open-source. This is not utopia. It is actually taking place thanks to projects that respond in concrete fashion to the basic needs of Man: food, home, health, energy, work and culture. The case of WASP is a pointer to changes that are occurring. An accumulation of futuristic technology geared towards a social application. It is also a clear demonstration of how an ethical vision is actually practicable within the logic of the business community. Moreover, it is the demonstration of how an ethical vision may become the driving force in developing projects and technologically advanced machines, which are then sold to feed the dream: to build heaven on earth.